Oxidized low density lipoprotein induces differentiation and adhesion of human monocytes and the monocytic cell line U937. - Frostegård, J (1990)
Hypercholesterolemia is a major risk factor for development of atherosclerosis. In experimental animals fed a high-cholesterol diet, monocytes adhere to the arterial endothelium and penetrate into the intima where they differentiate into macrophages and ingest lipids thus giving rise to fatty streaks, the earliest type of atherosclerotic plaque. Macrophages express few receptors for normal low density lipoprotein (LDL) but can take up oxidized LDL by way of a scavenger receptor. The present study was designed to investigate the possible role of oxidized LDL in recruitment of resident intimal macrophages. We found that oxidized LDL induced enhanced expression of major histocompatibility complex class II molecules on human monocytes and U937 cells, a well-established system for studies of monocytic differentiation. Oxidized LDL also induced enhanced expression of the surface antigen LeuM3 but caused decreased expression of CD4 antigen, a pattern compatible with expression of a more-differentiated macrophage-like phenotype. Oxidized LDL also initiated aggregation of monocytes and U937 cells and stimulated adhesion of U937 cells to cultured endothelial cells. The results indicate that oxidized LDL may contribute to development of atherosclerosis by inducing adhesion of monocytes to the arterial intima and by stimulating intimal monocytes to differentiate into resident macrophages.